(untitled) (Scientific journal of the Fergana State University, 2023)
This article aims to define the concept of "information technology discourse" in modern linguistics. The article analyzes the relationship of the language as a system and means of communication with the sphere of information technology, their mutual influence. The article contains linguapragmatic studies of approaches to the study of certain linguistic phenomena related to the field of information technology, including the use of communication devices, computers and the Internet. The definition of "IT discourse" is given on the basis of both all existing studies related to this field, and the author’s personal conclusions based on various research methods.